2009
DOI: 10.1007/s00701-009-0235-3
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondromas of the cervical spine in atypical location

Abstract: In the current article we review the available English literature by pubmed search engine on the topic of osteochondromas and their location in the cervical spine. The focus is to investigate the location of the lesions in cervical spine and to analyze clinical presentations and symptoms of patients, the aetiology and histopathology examination of the masses. In addition we report a rare illustrative case of a 62 year-old man with an osteochondroma of the cervical spine. The mass developed at a very slow rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Thus, there is a preponderance of primary spine tumors at this level among children. Schomacher et al provided a review of osteochondromas through 2007, 62 of which 43% were at the C1-2 level. Because of the preponderance of primary spinal tumors in this region and the early development of neurological deficits caused by local tumor growth patterns, we propose that atlantoaxial tumors in children constitute a distinct clinical entity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there is a preponderance of primary spine tumors at this level among children. Schomacher et al provided a review of osteochondromas through 2007, 62 of which 43% were at the C1-2 level. Because of the preponderance of primary spinal tumors in this region and the early development of neurological deficits caused by local tumor growth patterns, we propose that atlantoaxial tumors in children constitute a distinct clinical entity.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review identified osteochondromas in 40% of solitary benign tumors; a spinal location was noted for 1%-4% of cases. 62 Because up to 43% of spinal osteochondromas arise at the atlantoaxial level and 17% at C-7, they tend to occur at junctional-transitional areas. 13,39,51,59,60,64 Tubbs et al reported on a rare case of recurrent osteochondroma after incomplete resection.…”
Section: Primary Bone Tumors Affecting the Atlantoaxial Skeleton Of Cmentioning
confidence: 99%
“…49 There is a male predominance with a 3:1 male to female ratio. Osteochondromas are cartilage-capped bony growths, appearing in relation to the growth plate, and are either broad based or stalked.…”
Section: Osteochondromasmentioning
confidence: 99%
“…51,52 The cervical and thoracic regions are most commonly affected. 49 Clinical presentation: osteochondromas are usually asymptomatic, other than often producing a palpable mass with or without localized tenderness. Most lesions do not protrude into the spinal canal or neural foraminae, therefore neurological complications are uncommon.…”
Section: Osteochondromasmentioning
confidence: 99%
See 1 more Smart Citation